Trends in tree species selection for urban street planting: a thematic review - Maulan, Suhardi; Buang, Sabarudin; Mohd Tahir, Osman; Simangunsong, Nur Intan (e-IPH, 2024)
In major cities, street tree failures pose ongoing challenges related to user safety, tree management, and maintenance. This study evaluates trends in urban street tree selection by analysing 45 articles from 2019 to 2024 using keywords such as “street,” “tree species,” and “selection.” The thematic analysis identifies five key themes: species diversity, ecosystem services, climate adaptability, public perception, and management challenges. Findings highlight the need for a multifaceted approach, recommending criteria to reduce conflicts and ensure proper tree placement. The proposed framework aims to enhance urban tree resilience and coexistence with humans by emphasising genetic diversity and ecological benefits.